2014
DOI: 10.1037/cep0000011
|View full text |Cite
|
Sign up to set email alerts
|

The development of joke and irony understanding: A study with 3- to 6-year-old children.

Abstract: Previous research suggests that comprehending ironic utterances is a relatively late-developing skill, emerging around 5-6 years of age. This study investigated whether younger children might show an earlier understanding when ironic utterances are performed in familiar communicative situations, and investigated the relationships among irony comprehension, language, and theory of mind (ToM) abilities. A group of 100 children aged 3.0-6.5 years was presented with 4 types of puppet scenarios depicting different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 108 publications
8
65
1
1
Order By: Relevance
“…From this perspective, let us consider the relationship between irony and teasing. Angeleri and Airenti (2014) proposed the following componential definition of irony: irony is a non-literal utterance that is based on a common ground shared between interlocutors, focuses on an unexpected incongruity, and includes a teasing component.…”
Section: Humor Irony and Teasingmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, let us consider the relationship between irony and teasing. Angeleri and Airenti (2014) proposed the following componential definition of irony: irony is a non-literal utterance that is based on a common ground shared between interlocutors, focuses on an unexpected incongruity, and includes a teasing component.…”
Section: Humor Irony and Teasingmentioning
confidence: 99%
“…Our data indicate that young children may sometimes use ironic utterances appropriately. On the other hand, recent experimental studies have shown that children as young as 3 years old can understand the communicative, non-literal intent of ironic utterances ( Loukusa and Leinonen, 2008 ; Angeleri and Airenti, 2014 ).…”
Section: The Development Of Humor In Communication: the Role Of Theormentioning
confidence: 99%
“…Studies have shown that at around 5 or 6 years of age typically developing children begin to understand or detect that the ironic speaker means something very different (often the opposite) to what they have literally said (Hancock et al 2000;Harris and Pexman 2003;Keenan and Quigley 1999;Nakassis and Snedeker 2002;Winner and Leekam 1991). There is some evidence for comprehension at younger ages (Loukusa and Leinonen 2008;Recchia et al 2010), especially if the irony references failed expectations that can be directly perceived (Angeleri and Airenti 2014). Children's understanding of the ironic speaker's intent or purpose seems to emerge somewhat later, around age 7 or 8 (Ackerman 1983;Andrews et al 1986;Hancock et al 2000;Loukusa and Leinonen 2008).…”
Section: Pragmatic Developmentmentioning
confidence: 99%
“…Actually these experimental tasks are ToM tasks in the traditional definition and thus children have the traditional ToM results. In a study we designed an experimental task in which children had only to prove their comprehension of the communicative intention of ironic utterances, i.e., their non-literal meaning ( Angeleri and Airenti, 2014 ). For instance, if a character said to another character who had just broken a plate: “Your mommy will be happy!” children were expected to understand that the intended meaning was that the mother would be upset.…”
Section: Intersubjectivity and Tommentioning
confidence: 99%